Studying Information Technology in Organizations: Research Approaches and Assumptions - Orlikowski, Wanda J.; Baroudi, Jack J. (Information Systems Research, 1991)
We examined 155 information systems research articles published from 1983 to 1988 and found that although this research is not rooted in a single over-arching theoretical perspective, it does exhibit a single set of philosophical assumptions regarding the nature of the phenomena studied by information systems researchers, and what constitutes valid knowledge about those phenomena. We believe that a single research perspective for studying information systems phenomena is unnecessarily restrictive, and argue that there exist other philosophical assumptions that can inform studies of the relationships between information technology, people, and organizations. In this paper, we present two additional research philosophies for consideration-the interpretive and the critical-and for each we provide empirical examples to illustrate how they are used. We conclude by suggesting that much can be gained if a plurality of research perspectives is effectively employed to investigate information systems phenomena.